2017
DOI: 10.7567/jjap.56.088001
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic particle imaging for aerosol-based magnetic targeting

Abstract: Magnetic targeting is a strategy for improving the efficacy of therapeutic agents and minimizing the unwanted side effects by attaching the therapeutic agents to magnetic nanoparticles (MNPs) and concentrating them to the targeted region such as solid tumors and regions of infection using external magnetic fields. This study was undertaken to investigate the usefulness of magnetic particle imaging (MPI) for monitoring the effect of aerosol-based magnetic targeting by phantom experiments using a simple flow mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 15 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…Both MRI and MPI can benefit from these targeting strategies to enhance the concentration of imaging agent in a region-of-interest for increased binding probability to targets resulting in better imaging or localization of dose for better therapy. For example, Dames et al 2007 demonstrated the use of a shaped magnetic tip for targeted delivery of magnetic aerosol droplets to the lung [ 14 ] ( Figure 1 e) and Banura et al 2017 conducted a similar study with the addition of MPI to image the final biodistribution in the lungs after targeting [ 13 ] ( Figure 6 a). Other than the lungs, permanent magnets have been used to enhance delivery to tumors in other parts of the body.…”
Section: Magnetic-based Steering and Targeting Strategies Using Mpi Hardwarementioning
confidence: 99%
See 2 more Smart Citations
“…Both MRI and MPI can benefit from these targeting strategies to enhance the concentration of imaging agent in a region-of-interest for increased binding probability to targets resulting in better imaging or localization of dose for better therapy. For example, Dames et al 2007 demonstrated the use of a shaped magnetic tip for targeted delivery of magnetic aerosol droplets to the lung [ 14 ] ( Figure 1 e) and Banura et al 2017 conducted a similar study with the addition of MPI to image the final biodistribution in the lungs after targeting [ 13 ] ( Figure 6 a). Other than the lungs, permanent magnets have been used to enhance delivery to tumors in other parts of the body.…”
Section: Magnetic-based Steering and Targeting Strategies Using Mpi Hardwarementioning
confidence: 99%
“…( c ) Yu et al 2017 [ 12 ]—MPI image of SPIONs accumulated within a tumor. ( d ) Banura et al 2017 [ 13 ]—magnetic steering of magneto-aerosol with MPI as post-event verification. ( e ) Dames et al 2007 [ 14 ]—magnetic tip for targeted delivery of magnetic aerosol to lung.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This enabled localized treatment of tumors (potentially lung tumors) while sparing other tissues with non-specific SPION uptake 47 , 50 . Furthermore, because SPIONs can be shifted by magnetomotive forces from magnetic gradient fields, the therapeutic aerosol can be additionally moved in an image-guided fashion to a target region of the lung, increasing therapeutic efficiency 43 , 74 .…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, MPI is fully quantitative with zero depth attenuation as validated in prior work 22 , 30 thus is able to quantify the inhaled aerosol at any depth and with no view limitations since the low frequency magnetic excitation fields used in MPI penetrate completely through all types of tissue. Magnetic particle imaging has also been studied in many other applications (preclinical models) such as real-time MPI-guidance of catheters 40 , 41 , stroke diagnosis 35 , angiography 42 , lung perfusion 19 , lung ventilation 20 , 43 , cancer imaging 44 , stem cell tracking 8 , 18 , 45 , brain perfusion imaging 46 , magnetic hyperthermia 47 - 50 and gut bleed detection 51 .…”
Section: Introductionmentioning
confidence: 99%